The Effect and Related Mechanism of Action of Astragalus Compatible with Curcumin against Colon Cancer Metastasis in Mice - Jiafei Wu; Decai Tang (Gastroenterology Research and Practice)
Colon cancer (CC) is the third most common tumor worldwide. Colon carcinogenesis is strongly linked to inflammation. The initiation and progression of colon cancer may be influenced by epigenetic processes. Cancer metastasis is a multistep process involving several genes and their products. During tumor metastasis, cancer cells first enhance their proliferative capacity by lowering autophagy and apoptosis, and then, their capacity is stimulated by boosting tumors’ ability to take nutrients from the outside via angiogenesis. Traditional treatment focuses on eliminating tumor cells by triggering cell death or activating the immune system, which often results in side effects or chemoresistance recurrence. On the contrary, Chinese medicine theory considers the patient’s entire inner system and aids in tumor shrinkage while also taking into account the mouse’ general health. Because many Chinese herbal medicines (CHM) are consumed as food, using edible CHMs as a diet resource therapy for colon cancer treatment is a viable option. Two traditional Chinese herbs, Astragalus membranaceus and Curcuma zedoaria, are commonly utilized jointly in colon cancer preventive therapy. As a result, the anticancer effect of astragalus and curcumin (AC) on colon cancer suppression in an 18-week AOM-DSS colon cancer mouse model is investigated in this research. These findings may offer a scientific foundation for investigating colon cancer diagnostic biomarkers and therapeutic application of AC in colon cancer treatment. These studies also highlighted the potential effect and mechanism of AC in the treatment of colon cancer, as well as providing insight into how to effectively use it.